T2 Early-life respiratory tract infection and adult susceptibility to chronic mucus hypersecretion – a prospective 64 year national birth cohort study. (15th November 2016) - Allinson, JP; Hardy, R; Donaldson, GC; Shaheen, SO; Kuh, D; Wedzicha, JA
Abstract : Introduction: Smoking commonly triggers Chronic Mucus Hypersecretion (CMH) indicating both accelerated FEV1 decline and arguably early-phase COPD development. Early-life respiratory infections are proposed as another cause of adult CMH and also lead to impaired adult lung function. We investigated how smoking may modify the relationship between early-life infection and CMH across adult life. Methods: The MRC National Survey of Health and Development has prospectively studied a nationally representative sample of men and women since their birth during one week in March 1946 within England, Scotland and Wales. During early-life (ages 0 to 2 years) lower respiratory tract infection presence (EL-LRTI), father's occupational social class and estimated local pollution exposure were recorded for each study member. Smoking status and MRC questionnaire defined CMH were recorded six times between age 20 and 60–64 years. Random-effects logistic regression models for repeated measures were used to describe CMH trajectories across adult life by smoking status and EL-LRTI adjusting for sex, birth weight, early-life pollution exposure (high vs low) and social class (manual vs non-manual). Results: Amongst the 3617 individuals included (52% male; 63% ever-smokers) 25% experienced an EL-LRTI. CMH prevalence increased during adulthood (cumulative prevalence = 12%). Smokers had higher odds of CMH at all ages compared to non-smokers (Figure 1 ). For smokers and non-smokers, those with EL-LRTI had higher odds of CMH than those without EL-LRTI. There was evidence of an interaction between smoking status and EL-LRTI (Figure 1 ) such that at age 20 the effect of EL-LRTI (EL-LRTI+ve versus EL-LRTI–ve) was greater in non-smokers (OR = 4.0 (95% confidence interval (CI): 1.9 to 8.2; P < 0.001) than in smokers (OR = 1.48 CI: 0.8 to 2.6; P = 0.17). In non-smokers only the association between EL-LRTI and adult CMH lessened with ageing. Thus by age 60, the effect of EL-LRTI on the odds of having CMH (EL-LRTI+ve versus EL-LRTI–ve) amongst non-smokers (OR = 1.4 (CI: 0.8 to 2.4; P = 0.21)) and smokers (OR = 1.6 CI: 0.8 to 3.1; P = 0.15) was similar. Conclusion: Infants with respiratory infections become adults predisposed to developing CMH potentially reflecting pulmonary damage sustained during early-life or an overarching altered susceptibility to respiratory insults. This relationship is modulated by smoking and ageing.